The Role of EGFR Inhibition in the Treatment of Non-Small Cell Lung Cancer - Mandira Ray; Ravi Salgia; Everett E. Vokes (2009)
Abstract The identification of certain molecular mechanisms underlying lung carcinogenesis and progression has led to the development of targeted agents against different families of growth factors and receptors. The epidermal growth factor receptor (EGFR) is one such target for therapeutic exploitation. Inhibition of EGFR downstream signaling can be accomplished through two primary mechanisms: (a) the direct blocking of intracellular kinase activity with small-molecule tyrosine kinase inhibitors (TKIs) (e.g., gefitinib, erlotinib) and (b) the blocking of EGFR ligand binding using antibodies directed against the extracellular domain of the receptor (e.g., cetuximab). Resistance to available EGFR-targeted treatments has emerged as a substantial clinical issue in non-small cell lung cancer (NSCLC). Several novel agents with the potential to overcome such resistance are currently in clinical development, including irreversible EGFR TKIs, monoclonal antibodies, and TKIs directed against multiple signaling pathways. Here we discuss the clinical application of the currently available EGFR-targeted agents in NSCLC, the underlying mechanisms of resistance, and the novel agents in clinical development that may overcome resistance.